An Education for Life: Re-meaning of Integral Education Projects - Bataglia, Patricia Unger Raphael [UNESP]; Alves, Cristiane Paiva [UNESP]; Carmona Alvarado, Farid A.; Reyes-Ruiz, Lizeth (Colegio Mayor de Nuestra Senora del Rosario, 2024)
The Educational Resignification Project seeks the per-manent training of the teacher who thinks of education as a process, to transform the traditional educational space into a democratic and participatory space, with cooperative and interdisciplinary projects. Work was carried out for six months using the Educational Action Research-iae (Elliot, 1998); therefore, the topics of the program were established according to the interests and needs of the teachers and school directors. The implemen-tation was conducted with the educational community of a rural institution in São Paulo, where weekly workshops were developed around the questions: What would be the proposals for direct work with students? and What changes would affect pedagogical conceptions and practices of teachers and the relationships between all members of the school community (students, teachers, employees, family, etc.)? With the 217 students from 04 to 11 years old at this school, study scripts were developed based on their interests. The preliminary projects’ results showed it is possible to build education for citizenship and environmental awareness through actions that make sense for the school community.
Una educación para la vida: resignificación de proyectos educativos integrales
Uma educação para a vida: ressignificação de projetos educativos complementares
Keywords: comprehensiveness, complexity; education for life; educational projects; Resignification